Clinical Development of Immunotherapy for Small Cell Lung Cancer - Tao YU; Diansheng ZHONG (Chinese Journal of Lung Cancer, 2018)
Small cell lung cancer (SCLC), which accounts for about 15% of lung cancer cases, is an aggressive disease characterized by rapid growth and early widespread metastasis. Despite sensitive to chemotherapy and radiotherapy, SCLC is vulnerable to get resistant and has high recurrence rates. In recent years, immunotherapy has shown good antitumor activity, especially programmed death receptor-1/ligand-L1 (PD-1/L1) and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) Checkpoint inhibitors have changed the pattern of tumor treatment, and SCLC has high immunogenicity, high mutation load and other favorable immune factors, so immuno-checkpoint inhibitors may become an important breakthrough in SCLC treatment. This article will briefly review the clinical research of immunotherapy for small cell lung cancer.